Trends in the gameplay of European football players - Soroka, A. (Baltic Journal of Health and Physical Activity, 2014)
Background: The aim of this study was to compare the effectiveness of footballers who participated in the 2008 and 2012 European Championships. The study was conducted by analysis of basic technical and tactical game. Material/Methods: The observation method in the form of a kinematic game analysis system was used to collect necessary data. The research material was based on analysis of 304 players participating in the 2008 European Championships and 277 players in the 2012 European Championships, with each tournament consisting of 31 matches. Statistica software was used to apply the Student`s t-test for the independent groups. Results: Higher values of indicators determining player`s efficiency were found in the teams participating in the 2012 tournament; significant differences were found in the total number (p = 0.048) and accuracy (p = 0.034) of shots taken by the most successful teams, in the number (p = 0.044), efficiency (p = 0.002) and accuracy (p < 0.001) of passes as well as in the length of distance covered (p < 0.001). Conclusions: A systematic increase in the efficiency of passes in subsequent tournaments points to an upward trend of this element in the game. An increase was also noted in the numberof shots taken, which was accompanied by a decrease in shot accuracy. Modern football has become a fast team game with lots of passes of high reliability. Thus, training of young players should be focused on the development of playing techniques and motor skills.